Statin practices for ASCVD Prevention: A Cross-Sectional Analysis of Guideline Adherence in a High-Risk Local Patient Population - Kitchlew, Rizwana; Mukhtar, Haseeb; Farooqi, Mobeen; Ijaz, Muhammad Tayyab; Aslam, Zainab (Journal of the Pakistan Medical Association, 2025)
Objectives: To investigate the current practices of statin prescription and use for primary and secondary prevention of atherosclerotic cardiovascular disease. Method: The cross-sectional study was conducted at the Combined Military Hospital, Lahore, Pakistan, from December 2022 to June 2023, and comprised individuals with indication for statin therapy as per international guidelines. Data was collected using a self-designed questionnaire. The subjects were divided into primary prevention group A, comprising individuals aged 40 having one or more risk factors, and secondary prevention group B, comprising patients of all ages with a history of cardiovascular events. Data was analysed using SPSS 23. Results: Of the 397 subjects, 256(64.5%) were in group A and 141(35.5%) were in group B. Overall, 257(64.7%) subjects were males, 392(98.7%) were aged >40 years, and 275(69.3%) were taking statins, with a mean usage duration of 52±70 months. In group A, statin use prevalence was 148(57.8%) compared to 127(90.1%) in group B. Hypertension and diabetes mellitus was found in 293(73.8%) and 269(67.8%) participants, respectively. Individuals with a matriculation-level educational background had significantly higher odds of statin use compared to those below matriculation (p=0.044). Conclusion: There was a high frequency of atherosclerotic cardiovascular disease risk factors, like diabetes mellitus, hypertension and smoking, and statin use was significantly higher in the secondary prevention group compared to the primary prevention group. Key Words: Cardiovascular diseases, Hydroxymethylglutaryl-CoA reductase inhibitors, Prescriptions.